2023
DOI: 10.3390/ijms24065782
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Epigenetic Control of Aldosterone Synthase, CYP11B2 and 11-Hydroxylase, CYP11B1

Abstract: Aldosterone and cortisol serve important roles in the pathogenesis of cardiovascular diseases and metabolic disorders. Epigenetics is a mechanism to control enzyme expression by genes without changing the gene sequence. Steroid hormone synthase gene expression is regulated by transcription factors specific to each gene, and methylation has been reported to be involved in steroid hormone production and disease. Angiotensin II or potassium regulates the aldosterone synthase gene, CYP11B2. The adrenocorticotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…We reported that the hypomethylation status of CYP11B2 is negatively correlated with its mRNA level in APA [24]. CYP11B1 gene expression is also controlled by methylation in the adrenal gland [42]. Inder et al [8] reported a negative correlation between changes in the methylation status and mRNA level of HSD11B1 in the skeletal muscle of diabetic patients.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 70%
“…We reported that the hypomethylation status of CYP11B2 is negatively correlated with its mRNA level in APA [24]. CYP11B1 gene expression is also controlled by methylation in the adrenal gland [42]. Inder et al [8] reported a negative correlation between changes in the methylation status and mRNA level of HSD11B1 in the skeletal muscle of diabetic patients.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 70%
“…Research has also demonstrated that DNA methylation in promoters can be modulated to enable the expression of genes such as Cytochrome P450 Family 11 Subfamily B Member 2 (CYP11B2), which plays a significant role in blood pressure regulation ( 69 ). In spontaneous hypertensive rats, hypomethylation in the gene promoter of the cotransporter, Na+/K+/2Cl (NKCC), leads to an increase in NKCC levels, correlated with postnatal hypertension.…”
Section: Interaction Between Epigenetics and Hypertensionmentioning
confidence: 99%
“…Several hundred genes associated with ower color formation, containing transcription factors, transcriptional co-regulators, proteins involved in epigenetic control of gene expression, and microRNAs, have been well identi ed in model plant (Selva et al 2021; Guan et al 2021;Ren et al 2021;Takeda et al 2023). MicroRNAs (miRNA), a class of non-coding single strand molecules negatively regulating gene expressions both at transcriptional and posttranscriptional levels via cleaving targets or repressing protein translation, play important roles in ower organ development (Takeda et al 2023; Allahverdy and Rashidi 2023). Particularly, functional mature miRNAs are incorporated into Argonaute 1 (AGO1)-containing RNA-induced silencing complex (RISC) target endogenous transcripts, and cause mRNA degradation or translational repression in a sequence-speci c manner (Abel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Flower color, important objective in ornamental plant breeding, are controled by integrated effects of pigment composition, pH, cell shape, and copigmentation (Sinopoli et al 2019; Wang et al 2023;Li et al 2023). Several hundred genes associated with ower color formation, containing transcription factors, transcriptional co-regulators, proteins involved in epigenetic control of gene expression, and microRNAs, have been well identi ed in model plant (Selva et al 2021; Guan et al 2021;Ren et al 2021;Takeda et al 2023). MicroRNAs (miRNA), a class of non-coding single strand molecules negatively regulating gene expressions both at transcriptional and posttranscriptional levels via cleaving targets or repressing protein translation, play important roles in ower organ development (Takeda et al 2023; Allahverdy and Rashidi 2023).…”
Section: Introductionmentioning
confidence: 99%